2016
DOI: 10.1002/jmri.25297
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal quantitative MRI assessment of cortical damage in relapsing-remitting multiple sclerosis

Abstract: Out of the parameters studied, cortical T is best suited to detect cortical damage as an imaging surrogate of clinical disability in RRMS. J. Magn. Reson. Imaging 2016;44:1600-1607.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 36 publications
(61 reference statements)
4
28
2
1
Order By: Relevance
“…In the cortex, a region of interest (ROI) analysis showed that cortical T 1 prolongation and PD increase are present in early MS, indicating cortical damage . A separate study confirmed a relationship between cortical T 1 and the degree of disability in a relapsing‐remitting MS (RRMS) patient group, covering a range of disability severity and disease duration . Cortical demyelination at early MS stages can also be assessed with T 2 relaxometry, providing an alternative to the technically challenging T 1 and PD mapping …”
mentioning
confidence: 85%
See 3 more Smart Citations
“…In the cortex, a region of interest (ROI) analysis showed that cortical T 1 prolongation and PD increase are present in early MS, indicating cortical damage . A separate study confirmed a relationship between cortical T 1 and the degree of disability in a relapsing‐remitting MS (RRMS) patient group, covering a range of disability severity and disease duration . Cortical demyelination at early MS stages can also be assessed with T 2 relaxometry, providing an alternative to the technically challenging T 1 and PD mapping …”
mentioning
confidence: 85%
“…These patients were scored on the Expanded Disability Status Scale (EDSS) before the first scan . The patient pool comprised participants who had previously been included in cross‐sectional analyses, and we also used data obtained from a previous study into white matter …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MRI has long been used as a diagnostic tool, taking advantage of the MR signal’s dependence on underlying tissue properties, such as relaxation times and spin density, to provide natural contrast between tissue types. While many MR experiments are designed to provide qualitative weighting for a particular property, quantitative mapping is a useful diagnostic tool, for example, in oncology, cardiology, and neurology …”
Section: Introductionmentioning
confidence: 99%